2008
DOI: 10.1371/journal.pone.0002188
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Center Randomised Controlled Trial of Gatifloxacin versus Azithromycin for the Treatment of Uncomplicated Typhoid Fever in Children and Adults in Vietnam

Abstract: BackgroundDrug resistant typhoid fever is a major clinical problem globally. Many of the first line antibiotics, including the older generation fluoroquinolones, ciprofloxacin and ofloxacin, are failing.ObjectivesWe performed a randomised controlled trial to compare the efficacy and safety of gatifloxacin (10 mg/kg/day) versus azithromycin (20 mg/kg/day) as a once daily oral dose for 7 days for the treatment of uncomplicated typhoid fever in children and adults in Vietnam.MethodsAn open-label multi-centre rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 25 publications
(48 reference statements)
2
92
2
4
Order By: Relevance
“…A single daily dose of 10 mg/kg for 7 days has achieved cure in more than 90% of patients and short fever clearance times (341,480,537,538). Gatifloxacin targets both DNA gyrase and topoisomerase IV.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…A single daily dose of 10 mg/kg for 7 days has achieved cure in more than 90% of patients and short fever clearance times (341,480,537,538). Gatifloxacin targets both DNA gyrase and topoisomerase IV.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…The immunomodulatory effects of azithromycin may also be important by reversing the immunoparalysis seen in typhoid (28,29,560). Although some initial clinical studies were disappointing (561), subsequent randomized controlled trials have confirmed azithromycin to be equivalent or superior to chloramphenicol, fluoro-quinolones, and extended-spectrum cephalosporins for the management of uncomplicated typhoid fever and associated with a prompt resolution of clinical symptoms and low prevalence of relapse and convalescent fecal carriage (444,469,473,501,511,516,538). Doses have varied between 10 and 20 mg/kg/day for between 5 and 7 days, and the optimum dose and duration are yet to be determined.…”
Section: Azithromycinmentioning
confidence: 99%
“…Azithromycin has been used in the treatment of infections with S. Typhi and some enteric infections, and the accepted BSAC breakpoint MIC is 16 mg/liter for wild-type isolates. Azithromycin is suggested as an alternative to ciprofloxacin for treatment of cases that show reduced susceptibility to fluoroquinolones or treatment failure (2,8,9,18). Chayani et al recently showed that azithromycin was active against Salmonella and Shigella species, showing 100% sensitivity by the Etest and 83.33% by the disk diffusion methods (6).…”
Section: Case Reportmentioning
confidence: 99%
“…Un traitement hybride (ofloxacine à 15 mg/kg/j pendant 7 jours et azithromycine à 10 mg/kg/j pendant les 3 premiers jours) donnait des résultats intermédiaires. [30,31]. La gatifloxacine est une nouvelle fluoroquinolone qui a démontré une SYNTHÈSE REVUES activité bactéricide rapide sur les souches Cip SD et dont les CMI sont un peu plus faibles que celles de la ciprofloxacine sur ces mêmes souches Cip SD [26,31].…”
Section: Problèmes Posés Par L'identification Des Souches Résistantesunclassified
“…[30,31]. La gatifloxacine est une nouvelle fluoroquinolone qui a démontré une SYNTHÈSE REVUES activité bactéricide rapide sur les souches Cip SD et dont les CMI sont un peu plus faibles que celles de la ciprofloxacine sur ces mêmes souches Cip SD [26,31]. Au cours de ces deux essais, l'échec thérapeutique était documenté pour 3,5 % à 9 % des patients traités par la gatifloxacine (défervescence thermique obtenue entre 92 et 106 heures en moyenne), 9 % des patients traités par l'azithromycine (défervescence thermique obtenue en 106 heures), et 37,6 % des patients traités par le céfixime (défervescence thermique obtenue en 138 heures).…”
Section: Problèmes Posés Par L'identification Des Souches Résistantesunclassified